Entrepreneurial Orientation, Innovation and Performance: Unlocking Success for Small Business - Maya Yusnita; Satria Bangsawan; Ayi Ahadiat (Journal of International Conference Proceedings, 2025)
This study examines the effect of Entrepreneurial Orientation (EO) on Innovation and Small Business Performance in Indonesia, emphasizing the mediating role of Innovation. Drawing on the Resource-Based View (RBV), this research adopts a quantitative approach using Structural Equation Modeling (SEM-PLS4) with data collected from 100 small business owners across Southern Sumatra. The results demonstrate that EO has a significant positive impact on Innovation and Performance. Innovation also exerts a significant influence on Performance  and mediates the relationship between EO and Performance. These findings indicate that EO dimensions serve as critical drivers for enhancing innovation and achieving superior business outcomes. Theoretically, this study contributes to the validation and contextual extension of the RBV framework within Indonesian MSMEs. Empirically, it highlights Innovation as a strategic mechanism linking EO to performance improvement. Practically, the study underscores the importance of developing innovation capabilities to strengthen competitiveness and ensure sustainable growth in emerging economies